Inquiring long-term goal achievement and grit in a collectivist culture: a qualitative content analysis - Kailash Jandu; Rabindra Kumar Pradhan (Cogent Psychology)
The hitherto research on grit (i.e. passion and perseverance for long-term goal achievement) and its measurement, in psychological science, suffers from the issues of dimensionality and the possibility of different componential structures being present in collectivist culture vis-a-vis individualist culture. To address this, the present study aims to explore the factors influencing long-term goal achievement, an important aspect of the science of grit. The study further aims to examine the nature of grit in terms of its constituents from a qualitative perspective. A total of 48 respondents including five positive psychology experts and 43 higher education students from the Indian educational institutions took part in the study. Two different sets of open-ended questionnaires were used to gather data from the experts and the students. Inductive content analysis was used for analyzing the qualitative data. The findings revealed that both intrinsic factors (personal strengths, motivational factors, and goal factors) and extrinsic factors (socio-economic factors and familial factors) were essential for achieving long-term goals. Further, the components of grit included four constant strengths of perseverance, passion, purpose, and patience, and one variable strength of psychological flexibility. The present study contributes to the understanding of grit and long-term goal achievement from an in-depth qualitative perspective, broadening the current understanding of grit comprising of just perseverance and passion facets. The current study being a novel endeavor offers insights into the various possible constituents of grit existing in a collectivist setting which differ from the individualist context. Such a comprehensive understanding would enable the intervention developers to consider grit in its totality instead of just limiting to the original two-factor structure; while taking into account the role of personal, familial, and socio-economic factors in exhibiting the success behavior.